Boundaries and bridges: journeys of a postcolonial feminist in biblical studies - Dube, Musa Wenkosi (Resistance and visions, 2014)
The article underlines multiple-border crossings of the postcolonial world and the subsequent global diasporian identities. Born within the modern colonial history, the writer maps the journey of reading a book that had colonized her, and the continuity of colonizing ideology in the academic study of the Bible. Proposing to decolonize biblical studies from its Eurocentricism, the exclusive focus on the ancient Greco-Roman world in the study of biblical studies is problematized, since it brackets questions about modern colonialism; biblical mission texts’ attitudes towards the Other and towards the imperialism of their time are investigated; the use of gender to articulate positions of inequality is explored, and other ways of reading the Bible are proposed. In a bid to profile both the colonizing and the colonized Bible reader of modern times the writer’s current research reads letters of the modern colonial context, seeking to identify strategies of domination, resistance, collaboration and the emergence of hybridity in the modern colonial contact zone.